2020
DOI: 10.2147/pgpm.s275964
|View full text |Cite
|
Sign up to set email alerts
|

<p>Repurposing Drugs for COVID-19: Pharmacokinetics and Pharmacogenomics of Chloroquine and Hydroxychloroquine</p>

Abstract: Background A new coronavirus SARS-CoV-2 has been identified as the etiological agent of the severe acute respiratory syndrome, COVID-19, the source and cause of the 2019–20 coronavirus pandemic. Hydroxychloroquine and chloroquine have gathered extraordinary attention as therapeutic candidates against SARS-CoV-2 infections. While there is growing scientific data on the therapeutic effect, there is also concern for toxicity of the medications. The therapy of COVID-19 by hydroxychloroquine and chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 105 publications
2
11
0
Order By: Relevance
“…Taken together, the pharmacokinetic and ADME properties of CQ and HCQ complications such as heart failure and several non-reversible disorders have been previously, reported [ 45 ]. Our ADME and pharmacokinetic results confirmed previous data about pharmacokinetics and pharmacogenomics of CQ and HCQ [ 46 ]. The importance of the pharmacokinetic, ADME, and QSAR (for quantitative structure–activity relationship) assays was previously largely reported in the design and the assessment of several drugs [ 41 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 90%
“…Taken together, the pharmacokinetic and ADME properties of CQ and HCQ complications such as heart failure and several non-reversible disorders have been previously, reported [ 45 ]. Our ADME and pharmacokinetic results confirmed previous data about pharmacokinetics and pharmacogenomics of CQ and HCQ [ 46 ]. The importance of the pharmacokinetic, ADME, and QSAR (for quantitative structure–activity relationship) assays was previously largely reported in the design and the assessment of several drugs [ 41 , 47 , 48 ].…”
Section: Resultssupporting
confidence: 90%
“…Several pharmacogenetic biomarkers related to the metabolic pathway of drugs used for COVID-19 treatment have been described in the present review. In agreement with previous reports [ 7 , 8 , 9 ], there are variants in CYP2C8 , CYP2D6 , CYP3A4 , CYP3A5 , SLCO2B1 , ABCB1 , ABCC2 , CES1 , and G6PD that could help to improve the clinical outcome of the COVID-19. The scientific evidence supports the study of variants in CYP2D6, CYP3A4 , SLCO2B1 , ABCB1, and ABCC2 with the response to specific drugs ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Both drugs are widely metabolized in the liver by CYP2C8, CYP3A4, CYP3A5, and, to a lesser extent, by CYP2D6 [ 59 ]. Genetic variants of these enzymes have been previously described ( Table 1 ), and a study have suggested that CYP2C8 , CYP2C9, and CYP3A5 genetic variants influence chloroquine malaria treatment; however, there is not enough evidence of their impact on the chloroquine pharmacokinetics or response [ 8 , 60 ]. Transporters’ variants could be critical in the pharmacogenetics of chloroquine [ 61 ].…”
Section: Pharmacogenetics Of Antiparasitics Used For Covid-19 Treamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effectiveness of chloroquine and hydroxychloroquine remains controversial, with clinical evidence showing contrasting results. Some clinical trials reported therapeutic benefits of the drugs, while others trials showed the opposite, and others ones are still ongoing [ 60 ]. While there is growing studies to test therapeutic effect, there is also concern for toxicity and adverse effects of these medications, and thus FDA revoked the emergency-use authorization that allowed for chloroquine phosphate and hydroxychloroquine to be used to treat certain hospitalized patients with COVID-19 when a clinical trial was unavailable [ 61 ].…”
Section: Discussionmentioning
confidence: 99%